1994
DOI: 10.1063/1.467894
|View full text |Cite
|
Sign up to set email alerts
|

Understanding colloidal charge renormalization from surface chemistry: Experiment and theory

Abstract: In this paper we report on the charging behavior of latex particles in aqueous suspensions. We use static light scattering and acid-base titrations as complementary techniques to observe both effective and bare particle charges. Acid-base titrations'at various ionic strengths provide the pH dependent charging curves. The surface chemical parameters (dissociation constant of the acidic carboxylic groups, total density of ionizable sites and Stem capacitance) are determined from tits of a Stem layer model to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
128
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(140 citation statements)
references
References 25 publications
12
128
0
Order By: Relevance
“…For some of the aforementioned interaction measurements [12,17] this approach is appropriate, in other cases it may provide a very rough upper limit for the surface charge. If, on the other hand, the counterions due to the charged surfaces give a non-negligible contribution to the overall ionic strength, they have to be considered explicitly, for instance within a cell model [26,27]. Here, we concentrate on the former case of "high salt" and adopt the Basic Stern model [28], which has been shown to accurately describe titration data [29] obtained in the this regime for nominally nonporous, fully hydrated silica particles [24,25].…”
Section: Effective Charge Of Glass and Silica In Deionized Solutionsmentioning
confidence: 99%
“…For some of the aforementioned interaction measurements [12,17] this approach is appropriate, in other cases it may provide a very rough upper limit for the surface charge. If, on the other hand, the counterions due to the charged surfaces give a non-negligible contribution to the overall ionic strength, they have to be considered explicitly, for instance within a cell model [26,27]. Here, we concentrate on the former case of "high salt" and adopt the Basic Stern model [28], which has been shown to accurately describe titration data [29] obtained in the this regime for nominally nonporous, fully hydrated silica particles [24,25].…”
Section: Effective Charge Of Glass and Silica In Deionized Solutionsmentioning
confidence: 99%
“…The inflection point in the running effective charge of the macroion has been identified as another sensible boundary between free and bound counterions [36]. Yet another fruitful approach is to fit the effective one-component model (with a screened-Coulomb pair potential) to either the static structure factor measured in lightscattering experiments [14] or the pair distribution function computed in simulations of the primitive model [19,20,21,22,23]. A useful comparison of various criteria for defining effective charges is provided in ref.…”
Section: Modelmentioning
confidence: 99%
“…Similar ideas were subsequently applied to colloidal suspensions by Alexander et al [13], who demonstrated that strong association of counterions can significantly renormalize spherical macroion charges. Numerous experimental studies of deionized aqueous suspensions of highly charged spherical latex particles [14,15,16,17], integral-equation calculations [18], and simulation studies of the primitive model [19,20,21,22,23] have since confirmed the effective charge as a physically important parameter in the one-component model of colloidal suspensions.…”
Section: Introductionmentioning
confidence: 99%
“…It should be stressed that counterion condensation is a well-defined concept only within the cylindrical geometry of an infinite, uniformly charged thin rod [9,10]. In all other geometries, effective valences Z ef f can only be defined within some phenomenological convention [11,12]. In the case of spherical charge-stabilised colloids some recent direct measurements of the effective pair potential between polyions in the bulk of a suspension point to the validity of the functional form and range of the DLVO potential, provided Z ef f is considered to be an adjustable parameter, varying within a physically reasonable range [13].…”
Section: Introductionmentioning
confidence: 99%